The Preferency and Chemical Characteristics of Stick Products Fortification of Suckermouth Catfish Flour (Pterygoplichthys pardalis) - Nursinah Amir; Sahrul; Nursyamsi Djamaluddin; Irma Andriani (Hasanuddin University, 2022)
Suckermouth catfish (Pterygoplichthys pardalis) are found in Lake Tempe, Wajo Regency, but their existence has not been utilized so far and is even considered the cause of the loss of several endemic fish species in the lake. This study aims to determine the chemical characteristics and the preference level of sticks fortified with Suckermouth catfish (Pterygoplichthys pardalis) meal as an effort to utilize these fish. The research method used was experimental with treatment of SK (control without adding Suckermouth catfish flour), S1 (addition of 10 g of Suckermouth catfish flour), S2 (addition of 20 g of Suckermouth catfish flour), and S3 (addition of 30 g of Suckermouth catfish flour). The parameters observed were moisture, protein, fat, carbohydrate, and ash content, and the level of preference (hedonic test). The results showed that the panelists tended to say they really like the appearance and flavour of the stick S1 product, and very much like the taste and texture of the stick S3 product. The highest protein and water content was in S3 treatment, the highest ash and carbohydrate content was in SK treatment, and the highest fat content was in S1 treatment